Hans Christian Andersen in Trumpland - Juncker, Clara (Aktualitet - Litteratur, kultur og medier, 2019)
Hans Christian Andersen’s fairy tales have recently helped political and cultural observers figure out the Trump phenomenon. In post-election discussions of the Trump victory, frustrated Americans have drawn sustenance from Andersen’s fairy tale communities, both in “The Ugly Duckling” and most significantly in “The Emperor’s New Clothes.” Emotion takes center stage both in Andersen’s fairy tales and in representations of Trumpland in sculpture, cartoons, political commentary and in J. D. Vance’s best-selling “Hillbilly Elegy” (2016), set among Trump’s white, working-class supporters. In contemporary US culture, Andersen assists worried Americans in explaining the dysfunctional community of Trump voters and the mental instabilities of the President. Andersen also stresses resistance and celebrates those confronting community conventions. Ultimately, he sees literature as a safeguard against fakery and abuse and shows the path towards resistance and truth, despite the endeavors of the 45th US President to take his country in the opposite direction.